1979
DOI: 10.1002/aja.1001540402
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional architecture of the Golgi apparatus in Sertoli cells of the rat

Abstract: Glutaraldehyde-fixed testes were stained "en bloc" with the Ur-Pb-Cu technique of Thiéry and Rambourg ('76) or post-fixed and stained with the osmium tetroxide-potassium ferrocyanide method of Karnovsky ('71). Thin or thick (up to 3 micron) sections were examined with the Philips (301 or 400) EM or the high voltage EM. Stereopairs were prepared with photographs of tilted specimens (+/- 7 degrees). At low magnification, in thick sections (0.5-3 micron) stained with Ur-Pb-Cu, the whole Golgi apparatus formed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(154 citation statements)
references
References 37 publications
9
145
0
Order By: Relevance
“…It has been described as being continuous with either multiple transcisternae (Rambourg et al, 1979) or with only the trans-most cisterna in the stack (Griffiths and Simons, 1986). In our studies of both chemically fixed (Ladinsky et al, 1994) and rapidly frozen cells (Ladinsky et al, 1999;Marsh et al, 2001a), 3-D reconstructions have revealed tubules extending from multiple trans-cisternae but did not show this "traditional" TGN.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been described as being continuous with either multiple transcisternae (Rambourg et al, 1979) or with only the trans-most cisterna in the stack (Griffiths and Simons, 1986). In our studies of both chemically fixed (Ladinsky et al, 1994) and rapidly frozen cells (Ladinsky et al, 1999;Marsh et al, 2001a), 3-D reconstructions have revealed tubules extending from multiple trans-cisternae but did not show this "traditional" TGN.…”
Section: Introductionmentioning
confidence: 68%
“…These studies showed that all cisternae, including the trans-most, appear to be labeled (see for example, Geuze et al, 1984;Orci et al, 1987). However, individual thin sections rarely reveal the full extent of the cisternae in a given Golgi stack, because of convolution of the membranes and the presence of openings in the cisternae, such as fenestrae and "holes" (Rambourg et al, 1979;Rambourg and Clermont, 1990;Ladinsky et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Observation of the osmium-macerated specimens with high-resolution SEM also revealed the 3D ultrastructure of the tubuloreticular network in the pre-Golgi compartment in gonadotropes. The occurrence of the osmiophilic tubular network/elements in the proximity of the cis-face of the Golgi apparatus was identified by the stereoscopic observation of paired tilted images by high voltage TEM (9,(36)(37)(38). Based on the specific localization of a 53-58 kD protein, designated ERGIC-53 (42) or p58 (41) in the structure, this tubular network in the vicinity of the cis-Golgi is regarded as a discrete compartment, the ERGIC (3, 4, 18) or VTC (4).…”
Section: Discussionmentioning
confidence: 99%
“…Clusters of small vesicles observed next to such ER protrusions are considered as carriers of partly glycosylated proteins from the ER to the Golgi saccules [5,6,10,29]. The relationship of ER cisternae with the trans-aspect of the Golgi stacks, although described in some cells [8, 11-13, 30,31], has been given less attention. Novikoff et al [27,28] have emphasized the close association of ER cisternae with secretory vesicles and lysosomes on the trans-aspect of the Golgi apparatus (GERL concept).…”
Section: Introductionmentioning
confidence: 99%